Pengembangan model pembelajaran berbasis konstruktivistik kolaboratif mata pelajaran Pendidikan Agama Islam untuk meningkatkan kemampuan berfikir kritis siswa kelas V SDN Meri 1 Kota Mojokerto - Kajin, Sudar (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
Constructivism-Collaborative-based learning tools in improving critical thinking skills become an interesting learning model and assist the teacher's task in improving the effectiveness of learning, hence the need of an innovative learning tool to improve students' critical thinking ability. One learning tool that includes a set of planned learning experience that is arranged in a systematic, operational, and directed to help students master specific learning objectives is a collaborative-based Constructivist-Collaborative learning tool in improving the ability to think critically. The purpose of this research development is: 1.) To determine the feasibility of constructive collaborative lesson constructivist Islamic Education lesson according to peers. 2) To know the feasibility of constructive collaborative lesson of constructivism of Islamic Religious Education subject by Expert 3) To know the interest of the students of grade V of SDN Meri 1 Kota Mojokerto to the constructivist constructivism lesson of Islamic Education subject. The selection and use of collaborative constructivist-based learning models can effectively streamline and streamline the implementation of learning. For that purpose, collaborative constructivism-based learning model is absolutely necessary. Islamic Religion Education Learning Learning This collaborative constructivism based learning model has been refined based on analysis of trial data. Based on the steps that have been implemented can be concluded as follows. 1). Constructivist constructivist lesson of Islamic Religious Education is feasible according to peers. 2) constructivist constructivism lesson of Islamic Religious Education is feasible according to Expert 3) Grade V students of SDN Meri 1 Kota Mojokerto are interested in collaborative constructivist lesson of subjects of Islamic Religious Education